Survey of ICT and Education in Africa : Cameroon Country Report - Tchinda Josue, Tetang (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Cameroon is among the sub-Saharan African countries that are making enormous progress in the use of the ICTs in the various development sectors, including education. Private schools introduced ICTs into their curricula in the 1990s, but there is no specific policy guiding the teaching or use of ICTs in education, which has lead to each private school applying its own teaching method or program. ICTs were officially introduced into education in 2001 by the president. The Cyber Education Project launched since then by the government targets two sectors: secondary and tertiary education. Primary schools are not yet concerned. The project started a slowly, but is now gaining speed. The French government plays a great role in the implementation and is a major partner both financially and technically. Major achievements include establishing Multimedia Resources Centre's (MRCs) in universities, professional and technological schools, and some government secondary schools; training monitors to manage MRCs; creating learning platforms; interconnecting the six state universities; and establishing training units in professional schools and universities, some of which are now operational.